2013
DOI: 10.1097/qai.0b013e3182801081
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability and Feasibility of an HIV Preexposure Prophylaxis (PrEP) Trial With Young Men Who Have Sex With Men

Abstract: Background This study examined the feasibility of a combination prevention intervention for young men who have sex with men (YMSM), an anticipated target population for HIV pre-exposure prophylaxis (PrEP). Methods Project PrEPare, a pilot study using a randomized 3-arm design, compared an efficacious behavioral HIV-prevention intervention (3MV) alone, 3MV combined with PrEP (tenofovir/emtricitabine), and 3MV combined with placebo. Eligible participants were 18–22 year old HIV-uninfected men who reported unpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
153
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(159 citation statements)
references
References 17 publications
4
153
1
1
Order By: Relevance
“…Articles were excluded for not being a RCT or other suitable study, as specified in our inclusion criteria; not having the sufficient percentage of MSM in the study population; [137][138][139][140][141][142][143][144][145] not including a sufficient percentage of HIV-negative participants; [146][147][148][149][150][151][152][153][154][155][156] or not being an individually focused intervention, instead focusing on groups or structural factors. [157][158][159][160][161][162][163][164][165][166][167] Other reasons for exclusion, such as interventions not being brief, reporting a pilot trial, reporting non-HIV-specific data (e.g. if only alcohol-related outcomes were provided in a study assessing alcohol as well as HIV risk-related behaviours) or data were unobtainable despite our attempts to gain information from authors, were captured in our 'other' category.…”
Section: -106mentioning
confidence: 99%
“…Articles were excluded for not being a RCT or other suitable study, as specified in our inclusion criteria; not having the sufficient percentage of MSM in the study population; [137][138][139][140][141][142][143][144][145] not including a sufficient percentage of HIV-negative participants; [146][147][148][149][150][151][152][153][154][155][156] or not being an individually focused intervention, instead focusing on groups or structural factors. [157][158][159][160][161][162][163][164][165][166][167] Other reasons for exclusion, such as interventions not being brief, reporting a pilot trial, reporting non-HIV-specific data (e.g. if only alcohol-related outcomes were provided in a study assessing alcohol as well as HIV risk-related behaviours) or data were unobtainable despite our attempts to gain information from authors, were captured in our 'other' category.…”
Section: -106mentioning
confidence: 99%
“…MSM are considered by clinicians to be potential candidates for PrEP, 9 and studies have demonstrated that PrEP is an acceptable intervention to young MSM, 10,11 However, for PrEP to be an effective intervention, healthcare providers must be willing to prescribe this medication to youth. Potential providers of PrEP to adults have described a variety of concerns related to PrEP, including concerns about adherence, [12][13][14][15][16] development of viral resistance with incomplete adherence, 12,[14][15][16][17][18][19][20] high cost and insufficient coverage by insurance, 12,14,16,19,20 medication toxicity 12,14,17,18 and side effects, 16,17,19 efficacy outside of a clinical trial setting, 13,14,17,20 and risk compensation.…”
mentioning
confidence: 99%
“…ATN 082 enrolled 68 individuals (mean age 19.9 years) in a placebocontrolled study in which 58 individuals were randomised to a behavioural intervention alone or the behavioural intervention either with TDF/FTC or placebo. [29] Self-reported medication adherence averaged 62% (range 43 -83%), while rates of detectable plasma tenofovir ranged from 63.2% to 20% (weeks 4 -24). The most commonly reported reasons for missing doses included being away from home (60%), forgetting (50%) and being too busy (47%).…”
Section: Adolescents and Prepmentioning
confidence: 99%
“…The most commonly reported reasons for missing doses included being away from home (60%), forgetting (50%) and being too busy (47%). [29] ATN 110 enrolled 200 MSM aged 18 -22 years who were offered the same behavioural intervention with oral PrEP but in an openlabel manner. PrEP was well tolerated with minimal side-effects.…”
Section: Adolescents and Prepmentioning
confidence: 99%